Eonycteris major, Greater Dawn Bat - David, Waldien; Jayasilan, Mohd. Azlan (IUCN, 2021)
Eonycteris major is assessed as Near Threatened under criterion A2cd as the species global population is suspected to have declined by a rate of 25–29% over the past 12.9 years (three generations; GL = 4.3 years; Pacifici et al. 2013). Although data are limited as the species is rarely captured, the species decline is thought to result from the extent of disturbance at their cave roosts, loss of karst habitats, and the overall extensive forest loss and degradation on Borneo.